2013
DOI: 10.1017/s1041610213000045
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a cognitive intervention program in patients with mild cognitive impairment

Abstract: These results suggest that persons with MCI can improve their performance on cognitive and functional measures when provided with early cognitive training and it could persist in a long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 24 publications
2
73
0
10
Order By: Relevance
“…The systematic review identified five studies [26][27][28][29][30] (n = 408) that examined the effects on cognition of nonpharmacologic interventions (Appendix 4), including exercise, a holistic cognitive rehabilitation program and a multimodal intervention with stimulation and cognitive training sessions.…”
Section: Nonpharmacologic Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The systematic review identified five studies [26][27][28][29][30] (n = 408) that examined the effects on cognition of nonpharmacologic interventions (Appendix 4), including exercise, a holistic cognitive rehabilitation program and a multimodal intervention with stimulation and cognitive training sessions.…”
Section: Nonpharmacologic Interventionsmentioning
confidence: 99%
“…The summary of evidence for benefits of treatment is shown in Table 1. [19][20][21][22][23][24][25][26][27][28][29][30] A summary of the GRADE decision table can be found in Appendix 3 (available at www.cmaj.ca/lookup/suppl/doi:10.1503/ cmaj.141165/-/DC1), with detailed tables provided in the accompanying evidence review. 10 The recommendation applies to communitydwelling adults 65 years of age or older who do not have noticeable symptoms suggestive of mild cognitive impairment or dementia.…”
Section: We Recommend Not Screening Asymptomatic Older Adults (≥ 65 Ymentioning
confidence: 99%
See 2 more Smart Citations
“…Generally these findings suggest that the implementation of CT with aging adults with MCI is effective in improving various aspects of memory performance, executive functioning, processing speed, attention, fluid intelligence and subjects' perception of memory functioning, as measured by formal and task specific measures, as well as particular MRI measures of brain connectivity. In seven out of 26 randomized control trials where follow-up data was provided, positive effects on memory, recall, speed of processing and fluid intelligence were preserved anywhere from one week to two years following training [12][13][14].…”
Section: Introductionmentioning
confidence: 99%